Efficient generation of GGTA1-null Diannan miniature pigs using TALENs combined with somatic cell nuclear transfer - Wenmin Cheng; Heng Zhao; Honghao Yu; Jige Xin; Jia Wang; Luyao Zeng; Zaimei Yuan; Yubo Qing; Honghui Li; Baoyu Jia; Cejun Yang; Youfeng Shen; et al. (BMC, 2016)
Abstract Background α1,3-Galactosyltransferase (GGTA1) is essential for the biosynthesis of glycoproteins and therefore a simple and effective target for disrupting the expression of galactose α-1,3-galactose epitopes, which mediate hyperacute rejection (HAR) in xenotransplantation. Miniature pigs are considered to have the greatest potential as xenotransplantation donors. A GGTA1-knockout (GTKO) miniature pig might mitigate or prevent HAR in xenotransplantation. Methods Transcription activator-like effector nucleases (TALENs) were designed to target exon 6 of porcine GGTA1 gene. The targeting activity was evaluated using a luciferase SSA recombination assay. Biallelic GTKO cell lines were established from single-cell colonies of fetal fibroblasts derived from Diannan miniature pigs following transfection by electroporation with TALEN plasmids. One cell line was selected as donor cell line for somatic cell nuclear transfer (SCNT) for the generation of GTKO pigs. GTKO aborted fetuses, stillborn fetuses and live piglets were obtained. Genotyping of the collected cloned individuals was performed. The Gal expression in the fibroblasts and one piglet was analyzed by fluorescence activated cell sorting (FACS), confocal microscopy, immunohistochemical (IHC) staining and western blotting. Results The luciferase SSA recombination assay revealed that the targeting activities of the designed TALENs were 17.1-fold higher than those of the control. Three cell lines (3/126) showed GGTA1 biallelic knockout after modification by the TALENs. The GGTA1 biallelic modified C99# cell line enabled high-quality SCNT, as evidenced by the 22.3 % (458/2068) blastocyst developmental rate of the reconstructed embryos. The reconstructed GTKO embryos were subsequently transferred into 18 recipient gilts, of which 12 became pregnant, and six miscarried. Eight aborted fetuses were collected from the gilts that miscarried. One live fetus was obtained from one surrogate by caesarean after 33 d of gestation for genotyping. In total, 12 live and two stillborn piglets were collected from six surrogates by either caesarean or natural birth. Sequencing analyses of the target site confirmed the homozygous GGTA1-null mutation in all fetuses and piglets, consistent with the genotype of the donor cells. Furthermore, FACS, confocal microscopy, IHC and western blotting analyses demonstrated that Gal epitopes were completely absent from the fibroblasts, kidneys and pancreas of one GTKO piglet. Conclusions TALENs combined with SCNT were successfully used to generate GTKO Diannan miniature piglets.